Arte contemporânea na escola : práticas “educriativas” com a poética do lambe-lambe - Silva, Leide Fausta Gomes da (2019)
This article reports and discusses a pedagogical proposal developed in the field of artistic education, which aimed to bring contemporary art closer to the local culture. It documents a process of experimental teaching and learning that has occurred through “educative” practices exposed in the classroom and in urban spaces, constituted in: initial conversation, participatory explanation, creative action, urban intervention and self-assessment. Finally, it addresses considerations and impressions about work